Octagonal Defects at Carbon Nanotube Junctions - W. Jaskólski; M. Pelc; Leonor Chico; A. Ayuela (The Scientific World Journal)
We investigate knee-shaped junctions of semiconductor zigzag carbon nanotubes. Two dissimilar octagons appear at such junctions; one of them can reconstruct into a pair of pentagons. The junction with two octagons presents two degenerate localized states at Fermi energy (EF). The reconstructed junction has only one state near EF, indicating that these localized states are related to the octagonal defects. The inclusion of Coulomb interaction splits the localized states in the junction with two octagons, yielding an antiferromagnetic system.